Pelatihan Robot Soccer Bagi Siswa-Siswi SMKN 4 Kota Serang - Fikri Ardiyansah; Ihsan Faturrohman; Yoga Dwi Septiyanto; Siti Sypah Fauziyah; Khaila Mardina Fauziah Awalia; Prasta Mahrifatika; Repdhi Febriyan; Yudi Syah Pratama; Hijroh Tamamil Gina; Muhammad Reza Nugraha; Deva Adelya Prestanty; Irwanto Irwanto (Politeknik Kampar, 2023)
In the era of the Merdeka Curriculum, Industry 4.0 encompasses online learning, data analysis, artificial intelligence, the Internet of Things, digital skills development, project-based learning, and innovation. This enables a more personalized, efficient, and relevant education, while prioritizing equal access to technology and student data security and privacy. Community service in this context aims to provide introduction and training packaged in the form of a one-day workshop to attract the interest and talents of students at SMKN 4 Kota Serang to the basics of robotics, hardware components, software, as well as the design of hardware and software for soccer robots. The outcome of this activity is that students are able to understand the basic components, programming concepts of soccer robots, and can assemble a soccer robot module effectively and operate it. Many students are enthusiastic about this activity and express hope that it can continue so that a new robotics team can be formed at SMKN 4 Kota Serang, preparing them for upcoming robot competition championships.